Evaluation of river water quality using multivariate statistics and water quality indices: A case of Göynük canyon (Turkey) - Kareem J.; Leventeli Y. (Kuwait Journal of Science)
Natural and anthropogenic water pollution caused by heavy metals has become a major problem worldwide. As a result of these processes, many harmful heavy metals are mixed into the water and endanger the environment and human health. Therefore, this study aimed to investigate the hydrogeochemical properties of the stream waters of Göynük Canyon (Göynük Stream), which is located in southern Turkey, an important touristic region of Antalya. A total of 44 water samples were retained to evaluate the geochemical type, heavy metal contamination level, and suitability for drinking and irrigation of Göynük Canyon Stream waters. All samples were analysed by inductively coupled plasma mass spectrometry (ICP-MS), X-ray fluorescence (XRF), and multi-parameter portable water quality assessment. Analysed water samples were found to be of classes II and III in terms of overall water quality. The average hardness level is above the limit values. The results of geochemical analyses showed that the common water types in the region are Mg–Ca–HCO3, Ca–Mg–HCO3, Ca–Mg–HCO3–SO4, and Ca–Mg–HCO3–Cl-water facies. Most of the samples belong to the “rock weathering dominated” region represented in the Gibbs diagram. The hydrogen ion concentration (pH), electrical conductivity (EC), and total dissolved solids (TDS) values vary between respectively 6.5–7.9; 230.4–720.8 μS/cm, and 149–468 mg/L. Cations and anions followed the order Ca2+ > Mg2+ > Na+ > K+ and HCO3− > SO42− > Cl− > F− > NO3−. Heavy metal anomalies in water followed an increasing order: Cu < As < Pb < Ni < Ba < Fe < Cr < Mn < Zn < Sr. These heavy metals showed high index values (Poseidon index (PoS), contamination factor (CF), enrichment factor (EF), geochemical index (Igeo), heavy metals pollution index (HPI), contamination degree (Cd), in some water samples. There is a spatial anomaly in these locations related to limestone and ophiolite. This water can be used for irrigation purposes according to Wilcox, the United States salinity laboratory diagram (USSL), permeability index (PI), Kelly's ratio (KR), and Residual Sodium Carbonate (RSC). © 2024 The Author(s)